Agile human resource management practices and their role in achieving strategic superiority: An analytical study of the opinions of administrative leaders in a sample of private universities in the Kurdistan Region – Iraq - Haji, Zhinhat; Amin , Mahmoud (Humanities Journal of University of Zakho, 2023)
The study aims to identify the role of agile human resource management practices in achieving strategic excellence. In light of the study objective, the problem was summarized by a set of questions, namely; To what extent are the agile human resource management practices available in the universities under the study? To what extent are the dimensions of strategic excellence available in these universities? What is the nature of the correlation and influence between agile human resource management practices and the dimensions of strategic excellence in these universities? The study also aims to identify human resource management practices in these universities and explain its role in achieving strategic excellence. The study adopted the inductive approach (descriptive and analytical), as the data were collected by a questionnaire and distributed to a random sample of (135) people representing the administrative leaders in the universities under the study, and 103 questionnaires were retrieved from them, with a response rate of (76.3%). The data were statistically analyzed using the statistical package (SPSS: V. 22). The results of the study showed that the existence of a significant correlation between agile human resource management practices and strategic superiority at the overall level of the responding sample. In addition, the outcomes show that there is a significant relationship between the practices of agile human resources management and strategic excellence. The study presented a number of recommendations, the most important of which are: It is necessary for the universities under the study to pay great attention to the practices of agile human resource management because of their important role in implementing the organization's strategic plan and achieving strategic goals and thus affecting the achievement of strategic excellence in their universities. The study suggests that these universities should constantly update the compensation system in line with market requirements, because updating this system contributes to increasing the morale of workers and increasing their effectiveness at work.